Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
157 citations (Crossref) [2023-10-31] tex.ids: ISI:000279276600002, Rogers2010, lens.org/048-194-199-785-52X tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

Archaeology and the origins of human cumulative culture: a case study from the earliest Oldowan at Gona, Ethiopia - Stout, Dietrich; Rogers, Michael J.; Jaeggi, Adrian V.; Semaw, Sileshi (Current Anthropology, 2019)
The capacity of Homo sapiens for the intergenerational accumulation of complex technologies, practices, and beliefs is central to contemporary accounts of human distinctiveness. However, the actual antiquity and evolutionary origins of cumulative culture are not known. Here we propose and exemplify a research program for studying the origins of cumulative culture using archaeological evidence. Our stepwise approach disentangles assessment of the observed fidelity of behavior reproduction from inferences regarding required learning mechanisms (e.g., teaching, imitation) and the explanation of larger-scale patterns of change. It is empirically grounded in technological analysis of artifact assemblages using well-validated experimental models. We demonstrate with a case study using a toolmaking replication experiment to assess evidence of behavior copying across three 2.6 Ma Oldowan sites from Gona, Ethiopia. Results fail to reveal any effects of raw material size, shape, quality, or reduction intensity that could explain the observed details of intersite technological variation in terms of individual learning across different local conditions. This supports the view that relatively detailed copying of toolmaking methods was already a feature of Oldowan technological reproduction at ca. 2.6 Ma. We conclude with a discussion of prospects and implications for further research on the evolution of human cumulative culture.
69 citations (Crossref) [2023-10-31] tex.ids: ISI:000470895900002, Michael_Rogers48838567 tex.eissn: 1537-5382 tex.unique-id: ISI:000470895900002
Keywords: dept.ant; peer-reviewed

Imposed Form in the Early Acheulean? Evidence from Gona, Afar, Ethiopia - Stout, Dietrich; Liu, Cheng; Muller, Antoine; Rogers, Michael; Semaw, Sileshi (Journal of Archaeological Method and Theory, 2025)
Keywords: Acheulean; Ancient history; Anthropology; Archaeology; Early Stone Age; Ethnology; Geography; Handaxe; History; Large cutting tool; Lithic technology; Pick; Pleistocene; Shaping; Sociology; dept.ant

The Oldowan-Acheulian Transition: Is there a “Developed Oldowan” Artifact Tradition? - Semaw, Sileshi; Rogers, Michael; Stout, Dietrich (Sourcebook of Paleolithic Transitions: Methods, Theories, and Interpretations, 2009)
The phrase “Developed Oldowan” (DO) was originally coined by M. Leakey to describe a technologically “advanced Oldowan” artifact tradition, that preceded the Acheulian Industry. M. Leakey further identified three stages of the DO which she labeled as the DOA, DOB and DOC. The DO (sensu lato) has been generally recognized as transitional to the Acheulian, but the status of the DOB and the DOC remains unclear. In addition to a lack of clarity in terms of classification, the DO also suffers from a lack of secure radiometric dates, even at Olduvai where it was first identified. Despite such shortcomings, archaeologists still assign assemblages into the DO, as supposedly “intermediate” or transitional between the Oldowan and the Acheulian. However, a closer look at the DO assemblages from Olduvai Gorge and other sites in Africa and the Middle East shows that the artifacts assigned into this tradition are not technologically drastically different from the preceding Oldowan. Probably the flaking characteristics of the raw material types (e.g., quartzite and limestone, and to a lesser extent basalt) and the original shape of the cobbles used by hominins may have played a major role in the final shape of the “distinctive” artifact types (such as spheroids/subspheroids) used for assigning assemblages into the DO. Further, both the DOB and the Acheulian appeared ˜1.7 million years ago (Ma) in the archaeological record, making it unlikely that the DO is a transitional artifact tradition that preceded the Acheulian. Our preliminary evaluation of the archaeological record at Gona, Ethiopia and elsewhere suggests a fairly abrupt appearance of the Acheulian after a temporally rapid transition from the Oldowan.
Citation Key Alias: lens.org/001-307-927-954-428
Keywords: Developed Oldowan; Early Acheulian; Oldowan; Oldowan-Acheulian transition; dept.ant

Raw material selectivity of the earliest stone toolmakers at Gona, Afar, Ethiopia - Stout, Dietrich; Quade, Jay; Semaw, Sileshi; Rogers, Michael J.; Levin, Naomi E. (Journal of Human Evolution, 2005)
Published evidence of Oldowan stone exploitation generally supports the conclusion that patterns of raw material use mere determined by local availability. This is contradicted by the results of systematic studies of raw material availability and use among the earliest known archaeological sites from Gona, Afar, Ethiopia. Artifact assemblages from six Pliocene archaeological sites were compared with six random cobble samples taken from associated conglomerates that record pene-contemporaneous raw material availability. Artifacts and cobbles were evaluated according to four variables intended to capture major elements of material quality: rock type, phenocryst percentage, average phenocryst size, and groundmass texture. Analyses of these variables provide evidence of hominid selectivity for raw material quality. These results demonstrate that raw material selectivity was a potential component of Oldowan technological organization from its earliest appearance and document a level of technological sophistication that is not always attributed to Pliocene hominids. (c) 2004 Elsevier Ltd. All rights reserved.
134 citations (Crossref) [2023-10-31] Citation Key Alias: pop00050 tex.type: [object Object]
Keywords: Africa; Cognition; East Africa; Eastern Hemisphere; Ethiopia; Gona; Hominidae; Lithic technology; Oldowan; Pene; Pliocene; Raw materials; Sub-Saharan Africa; World; dept.ant; human activity; lithic fragment; peer-reviewed

The Early Acheulean ~1.6–1.2 Ma from Gona, Ethiopia: Issues related to the emergence of the Acheulean in Africa - Semaw, Sileshi; Rogers, Michael J.; Cáceres, Isabel; Stout, Dietrich; Leiss, Amanda C. (The Emergence of the Acheulean in East Africa and Beyond: Contributions in Honor of Jean Chavaillon, 2018)
Konso in Ethiopia and Kokiselei in Kenya, both dated to ~1.7 million years ago (Ma), and FLK West, a recently reported site from Olduvai dated to 1.7 Ma, are the earliest Acheulean sites known in East Africa. Ongoing archaeological investigations at Gona, in the Afar Depression of Ethiopia, have also produced early Acheulean stone assemblages at several sites, estimated to ~1.6–1.2 Ma. A number of sites, including BSN-12 and OGS-12, have yielded archaeological materials comparable to the earliest Konso artifacts. The stone assemblages from the Gona sites consist of crudely made handaxes, cleavers, and picks, as well as Mode I (Oldowan) cores, and débitage. A variety of raw materials were exploited at Gona, with trachyte, rhyolite, and basalt being the most common.Our understanding of the behavioral and ecological background for the emergence of the Acheulean is still limited. Preliminary comparisons of BSN-12 and OGS-12 with other early Acheulean sites demonstrate variability in paleoecological settings as well as raw material use. Current archaeological evidence indicates that early Homo erectus/ergaster use of this new technology was already in place in East Africa ~1.75 Ma. At Gona and elsewhere in Africa, continued survey and excavations are needed to document sites with potential for yielding archaeological traces that will help our understanding of the Oldowan–Acheulean transition, the identity of the toolmakers, and the function of the early Acheulean Large Cutting Tools (LCTs).
Citation Key Alias: lens.org/010-344-387-916-971
Keywords: Ethiopia; Gona; Oldowan–Acheulean transition; Technical behaviors; dept.ant

Paleoenvironments of the earliest stone toolmakers, Gona, Ethiopia - Quade, Jay; Levin, Naomi E; Semaw, Sileshi; Stout, Dietrich; Renne, Paul R; Rogers, Michael J; Simpson, Scott W (Geological Society of America Bulletin, 2004)
Fluvio-lacustrine sediments of the Hadar and Busidima Formations along the northern Awash River (Ethiopia) archive almost three million years (3.4 to <0.6 Ma) of human evolution, including the earliest documented record of stone toolmaking at 2.5-2.6 Ma. This paper brings together sedimentologic and isotopic evidence for the paleoenvironmental context of early hominids from both formations, but with particular emphasis on the setting for the early toolmakers. The pre-2.92 Ma record (Hadar Formation) is characterized by low-gradient fluvial, paludal, and lacustrine deposition in an undissected topography most analogous to reaches of the modern middle Awash River near Gewane. The Gona area experienced repeated deep dissection and aggradation by the Awash River, starting between 2.92 and ca. 2.7 Ma and continuing through the top of the record at <0.6 Ma (Busidima Formation). Each aggradational succession is 10-20 m in thickness and fines upward from well-rounded conglomerates at the base to capping paleosols at the top. During this period the ancestral Awash represented by these fining upward sequences was dominantly meandering and flowed northeast, as it does today. Smaller channels tributary to the axial Awash system are also extensively exposed in the Busidima Formation. Compared to the axial-system conglomerates, the tributary channels transported finer, less mature volcanic clasts mixed with abundant carbonate nodules reworked from adjacent badlands. Stone artifacts (Oldowan; 2.6-2.0 Ma) at the oldest archaeological sites are only associated with the axial Awash system, in the bedded silts or capping paleosols of the fining upward sequences. The implements were made from rounded cobbles from the channels, but manufacture and use of the tools was always away from the channel bars, on the nearby sandy banks and silt-dominated floodplains. Archaeological sites higher in the record (Acheulian; <1.7 Ma) occur in similar axial river contexts, as well as along tributary channels further removed from artifact raw material sources. Mature paleosols in the Hadar and Busidima Formations are mostly pale to darkbrown Vertisols typified by abundant clay slickensides, pseudo-anticlinal and vertical fracturing, and carbonate nodules. Such calcic Vertisols are common in the region today, demonstrating that the paleoclimate over the past 3.4 m.y. has been semi-arid and strongly seasonal. Carbon isotopic results from pedogenic carbonates in the Vertisols allow reconstruction of the proportion of C3 plants (trees and shrubs) to C4 plants (grasses) through time. The δ 13C results from the Hadar Formation prior to 2.9 Ma range from -9.3‰ to -4.1‰, indicating a dominantly forested environment but with locally substantial (average 34%) grasses on the Awash floodplain. The δ13C values from soil carbonate in the lower Busidima Formation (2.7-1.6 Ma) increase (-6.5‰ to -2.7‰) in floodplain paleosols, indicating ∼ 50% average grass cover. Vertisols of the upper Busidima Formation (< 1.6 Ma) formed on gently sloping alluvial fans adjacent to the Awash floodplain and display even more positive δ13C values, up to -1.8‰, showing that grassland dominated the margins of the active Awash floodplain. © 2004 Geological Society of America.
102 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-788-106-966-805 tex.type: [object Object]
Keywords: Africa; Awash; Axial flow; Carbon isotopes; Cenozoic; Deposition; Early hominids; East Africa; Eastern Hemisphere; Ethiopia; First stone tools; Gona; Human evolution; Oldowan; Paleoenvironment; Paleoenvironments; Rivers; Sediments; Sub-Saharan Africa; Tools; World; dept.ant; fluviolacustrine deposit; hominid; human activity; lithic fragment; paleoenvironment; tool use

2.6-Million-year-old stone tools and associated bones from OGS-6 and OGS-7, Gona, Afar, Ethiopia - Semaw, Sileshi; Rogers, Michael J; Quade, Jay; Renne, Paul R; Butler, Robert F; Dominguezrodrigo, Manuel; Stout, Dietrich; Hart, William S; Pickering, Travis Rayne; Simpson, Scott W (Journal of Human Evolution, 2003)
327 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000185995000005, lens.org/105-776-516-547-29X tex.type: [object Object]
Keywords: Afar; Animalia; Bone fragments; Cutmarks; Earliest stone tools; Ethiopia; Gona; Hominidae; Mammalia; Ounda Gona; Pliocene; archaeological evidence; artifact; bone; dept.ant; peer-reviewed; tool use

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
40 citations (Crossref) [2023-10-31] Place: United States Semaw, Sileshi. Centro Nacional de Investigacion sobre la Evolucion Humana (CENIEH), Sierra de Atapuerca 3, 09002 Burgos, Spain. Semaw, Sileshi. Stone Age Institute and CRAFT Research Center, 1392 W. Dittemore Rd., Gosport, IN 47408, USA. Rogers, Michael J. Department of Anthropology, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. Simpson, Scott W. Department of Anatomy, Case Western Reserve University School of Medicine, Cleveland, OH 44106, USA. Simpson, Scott W. Laboratory of Physical Anthropology, Cleveland Museum of Natural History, Cleveland, OH 44106, USA. Levin, Naomi E. Department of Earth and Environmental Sciences, University of Michigan, 1100 North University Avenue, Ann Arbor, MI 48109, USA. Quade, Jay. Department of Geosciences/Desert Laboratory, University of Arizona, Tucson, AZ 85721, USA. Dunbar, Nelia. New Mexico Bureau of Geology and Mineral Resources, Earth and Environmental Science Department, New Mexico Tech, 801 Leroy Place, Socorro, NM 87801-4796, USA. McIntosh, William C. New Mexico Bureau of Geology and Mineral Resources, Earth and Environmental Science Department, New Mexico Tech, 801 Leroy Place, Socorro, NM 87801-4796, USA. Caceres, Isabel. Universitat Rovira i Virgili (URV), Avinguda de Catalunya 35, 43002 Tarragona, Spain. Caceres, Isabel. IPHES, Institut Catala de Paleoecologia Humana i Evolucio Social, Zona Educacional 4-Campus Sescelades URV (Edifici W3), 43007 Tarragona, Spain. Stinchcomb, Gary E. Watershed Studies Institute and Department of Earth and Environmental Sciences, Murray State University, Murray, KY 42071, USA. Holloway, Ralph L. Department of Anthropology, Columbia University, 1200 Amsterdam Ave., New York, NY 10027, USA. Brown, Francis H. The University of Utah, 201 South Presidents Circle Room 201, Salt Lake City, UT 84112, USA. Butler, Robert F. Department of Physics, University of Portland, Portland, OR 97203, USA. Stout, Dietrich. Department of Anthropology, Emory University, 1557 Dickey Drive, Atlanta, GA 30322, USA. Everett, Melanie. Chevron Energy Technology Company, 1500 Louisiana St., Houston, TX 77002, USA.
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull